THE ROLE OF HEALTH INSURANCE IN RETIREMENT SERVICES : ADDRESSING HEALTH RISKS AND CARE COSTS - Elmi Faizatul Waqi'ah (Assets Journal: Journal of Economic and Business, 2024)
This journal proposes an interdisciplinary approach that aims to address health risks and reduce medical costs by considering public health, health economics, health policy, and medical technology innovation. This research identifies strategies that can improve public health and manage the increasing burden of care costs, with a focus on holistic and sustainable solutions. The literature review presents public health risks, notes the impact of care costs on the health system, and highlights the importance of an interdisciplinary approach in achieving sustainable health goals. The author outlines key strategies for addressing health risks, such as disease prevention, chronic disease management, and the role of medical technology in meeting these challenges, with appropriate methodologies. The case studies provide examples of successful implementation of public health programs to address health risks and reduce treatment costs, including the implementation of new medical and effective health policies. Through analysis and discussion, this study provides insight into the main findings and implications of the proposed interdisciplinary approach. In conclusion, an interdisciplinary approach can become a solid foundation for addressing health risks and reducing treatment costs. Holistic solutions offered through the integration of various disciplines can become a reference for making meaningful health decisions for the future. This study provides recommendations for next steps in achieving optimal public health and higher cost-efficiency of care.